Ultrasonic Vocalizations in Mice During Exploratory Behavior are Context-Dependent - Mun, Ho-Suk; Lipina, Tatiana V.; Roder, John C. (Frontiers in Behavioral Neuroscience, 2015)
While rat ultrasonic vocalizations (USVs) are known to vary with anticipation of an aversive versus positive stimulus, little is known about USVs in adult mice in relation to behaviors. We recorded the calls of adult C57BL/6J male mice under different environmental conditions by exposing mice to both novel and familiar environments that varied in stress intensity through the addition of bright light or shallow water. In general, mouse USVs were significantly more frequent and of longer duration in novel environments. Particularly, mice in dimly-lit novel environments performed more USVs while exhibiting unsupported rearing and walking behavior, and these calls were mostly at high frequency. In contrast, mice exhibited more low frequency USVs when engaging in supported rearing behavior in novel environments. These findings are consistent with data from rats suggesting that low-frequency calls are made under aversive conditions and high-frequency calls occur in non-stressful conditions. Our finding increase understanding of acoustic signals associated with exploratory behaviors relevant to cognitive and motivational aspects of behavior.